Morphological, functional, and biomechanical progression of LV remodelling in a porcine model of HFpEF. (November 2022) - Zheng, Yu; Chan, Wei Xuan; Charles, Christopher J.; Richards, Arthur Mark; Lee, Lik Chuan; Leo, Hwa Liang; Yap, Choon Hwai
Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) accounts for about half of heart failure cases, but the progression of cardiac biomechanics during pathogenesis is not completely understood. We investigated a published porcine model of HFpEF, generated by progressive constriction of an aortic cuff causing progressive left ventricle (LV) pressure overload, and characterized by hypertrophy, diastolic dysfunction and overt HF with elevated plasma beta natriuretic peptide (BNP). We characterized morphological and functional features and performed image-based finite element modelling over multiple time points, so as to understand how biomechanics evolved with morphological and functional changes during pathogenesis, and to provide data for future growth and remodeling investigations. Results showed that the hypertrophic responses quickly manifested and were effective at preventing an elevation of systolic myocardial stresses, suggesting active compensated remodeling. Consequent to the hypertrophy, diastolic myocardial stresses decreased despite the elevations in diastolic pressures. The left ventricle hypertrophy (LVH) myocardium also exhibited a quick elevation of active tension at the onset of the disease. There was a progressive and significant decrease in myocardial strain, which was more significant in the longitudinal direction. Further, elevated myocardial stiffness and diastolic pressures, which reflected diastolic dysfunction, also manifested, but this was delayed from the onset of the disease. Correlation analysis showed that hypertrophy was closely correlated to systolic pressure, active tension and systolic myocardial stress, suggesting that these factors may play a role in initiating hypertrophy. Myocardial stiffness was weakly correlated to LV pressures and myocardial stresses.